The Regional Competitiveness Analysis in Turkey - Albayrak, Ayse Nur; Erkut, Gulden (Yildiz Technical Univ, Fac Architecture, 2010)
The competitiveness approach has been on the research agenda following the transformation of the global economic structure. Cities and regions are competing with each other as companies do in order to increase their competitiveness. Innovation and, the urban social and cultural infrastructure are influential on this process. In a related context, regions differ in their ability to complete and this is connected to their qualities and the differences in their development levels. In this research paper, first Turkey's regions are classified according to their competitiveness level and then the characteristics of these regions are defined. To this aim, a regional competitiveness index is used which has been developed using principle component analysis and hierarchical clustering analysis. As a result of this research, five regional competitiveness groups have been determined, based on NUTS II level regions of Turkey. We suggest that regional policies should be developed considering the competitiveness level and global competitiveness of these five groups.
Keywords: Regional competitiveness; regional policy; regional development; NUTs II regions